Performance measurements of cylindrical- and spherical-helical cross-flow marine hydrokinetic turbines, with estimates of exergy efficiency. (February 2015) - Bachant, Peter; Wosnik, Martin
Abstract: Power and drag (or thrust) measurements were performed in a towing tank for two different helical cross-flow marine hydrokinetic energy conversion devices—a cylindrical Gorlov Helical Turbine (GHT) and a Lucid Spherical Turbine (LST). The turbines are compared with respect to their various design parameters, with the GHT overall operating at higher power and drag coefficients. An estimate for the exergy efficiency of a turbine in free flow is formulated using momentum theory, and this quantity is computed for both devices. The GHT's exergy efficiency advantage over the LST was higher than that based on the power coefficient. Momentum theory-based blockage corrections were applied to the measurements and compared with the non-corrected data. The results presented here will help increase the amount of experimental data for helical devices in the literature, which is necessary for the development of more accurate engineering tools that take into account the unique three-dimensional nature of these devices. Highlights: Experimental measurements for performance of two cross-flow turbines are presented. A momentum theory-based exergy efficiency metric is derived and computed. A momentum theory-based blockage correction is applied to the data for comparison.